2014
DOI: 10.1002/bem.21880
|View full text |Cite
|
Sign up to set email alerts
|

Effects of GSM‐modulated 900 MHz radiofrequency electromagnetic fields on the hematopoietic potential of mouse bone marrow cells

Abstract: Studies describing the influence of radiofrequency electromagnetic fields on bone marrow cells (BMC) often lack functional data. We examined the effects of in vivo exposure to a Global System for Mobile Communications (GSM) modulated 900 MHz RF fields on BMC using two transplantation models. X-irradiated syngeneic mice were injected with BMC from either RF-field-exposed, sham-exposed or cage control mice. Twelve weeks after transplantation, no differences in thymocyte number, frequency of subpopulations and ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…Similarly, Nasta [ 67 ] found that the same one-month RF treatment protocol did not affect the B-cell peripheral compartment (T1 and T2 cells, mature follicular and marginal zone B-cells) or antibody (IgM and IgG) production. Most recently, Rosado [ 68 ] found no effects of 900 MHz-exposed bone marrow cells on their long-term (3-month) ability to reconstitute peripheral T and B cells, and no differences in thymocyte number, frequency, or proliferation. Collectively, these rodent studies suggest that the immunosystem will not be impacted by TEMT in humans, especially since only the head will be exposed to RF treatment.…”
Section: Section Ii: Pre-clinical Animal/cell Culture Studies Of Emf mentioning
confidence: 99%
“…Similarly, Nasta [ 67 ] found that the same one-month RF treatment protocol did not affect the B-cell peripheral compartment (T1 and T2 cells, mature follicular and marginal zone B-cells) or antibody (IgM and IgG) production. Most recently, Rosado [ 68 ] found no effects of 900 MHz-exposed bone marrow cells on their long-term (3-month) ability to reconstitute peripheral T and B cells, and no differences in thymocyte number, frequency, or proliferation. Collectively, these rodent studies suggest that the immunosystem will not be impacted by TEMT in humans, especially since only the head will be exposed to RF treatment.…”
Section: Section Ii: Pre-clinical Animal/cell Culture Studies Of Emf mentioning
confidence: 99%
“…Nowadays, non-ionizing radiation is widely spread; its most important source is the microwave-radiation produced by mobile phone devices, which in recent years have been used by most of the world's population [1].…”
Section: Introductionmentioning
confidence: 99%
“…Одной из cиcтем, котоpая чутко pеагиpует на изменение окpужающиx уcловий cpеды, являетcя cиcтема кpови. В pяде pабот показаны изменения в клеткаx кpови и коcтного мозга в ответ на дейcтвие ЭМИ , генеpиpуемого на чаcтоте pаботы cотовыx телефонов [13][14][15].…”
unclassified